Long-term changes in the production by estuarine macrobenthos affected by multiple stressors - Dolbeth, M. (2011)
The macrobenthic production of an estuarine system was evaluated over a 14-year study period in a seagrass bed and in a sandflat. Over this period, the estuary suffered severe eutrophication and extreme weather events with important impacts on the community, impairing system functioning and ultimately the goods and services provided by the estuary (decline in the seagrass bed, decreased community production and/or a boost in the production by opportunist species, such as Hydrobia ulvae). Following the anthropogenic impacts, management measures were introduced which allowed a gradual recovery of the seagrass bed and a new macrobenthic community structure manifested by production increases of slow-growing species, such as Scrobicularia plana and Hediste diversicolor. There was a gradual re-orientation of energy into population biomass instead of population density but this was not translated into higher community production, mainly due to the decreased production of opportunist species (H. ulvae and several polychaetes). Several weather extreme events occurred during this post-mitigation phase - floods, heatwaves and droughts, all of which had negative impacts on macrobenthic dynamics and production. The heatwaves led to the greatest decreases in macrobenthic production, mainly due to S. plana perhaps associated with its physiological intolerance of higher temperatures. The prolonged drought that followed the heatwaves maintained low levels of production by S. plana and H. ulvae. With climate change, the frequency and intensity of extreme weather events are likely to increase worldwide so that the recovery of impacted/disturbed systems from impacts such as eutrophication may be seriously affected by these additional stressors, compromising attempts to improve the ecological quality of estuarine ecosystems.